Novel strategy for cystitis glandularis: Oral treatment with cyclooxygenase‐2 inhibitor. (30th May 2016) - Takizawa, Nae; Matsuzaki, Tomoaki; Yamamoto, Teppei; Mishima, Takao; Miyasaka, Chika; Tanaka, Susumu; Kinoshita, Hidefumi; Uemura, Yoshiko; Yamada, Hisao; Matsuda, Tadashi
Abstract: Cystitis glandularis, a proliferative disease of the bladder, is resistant to antibiotics, non‐steroidal anti‐inflammatory drugs, anti‐allergy drugs and transurethral resection. Cystectomy or partial cystectomy is occasionally required for refractory cystitis glandularis. It has not been defined if cystitis glandularis is a premalignant lesion. We experienced a case of remission from cystitis glandularis after combination of oral treatment with selective cyclooxygenase‐2 inhibitor, celecoxib and transurethral resection. Immunohistochemistry showed positive signals of cyclooxygenase‐2 in the epithelium of pretreatment specimens, suggesting the pathophysiological role of cyclooxygenase‐2 in cystitis glandularis. Here, we show the effectiveness of celecoxib against cystitis glandularis for the first time. Celecoxib could be one of the therapeutic strategies for cystitis glandularis.